Konstruksi Teologi Bagi Gereja dan Israel Dalam Roma 11:25-27 - Daniel Lindung Adiatma (Predica Verbum: Jurnal Teologi dan Misi, 2021)
Romans 11:25-27 is part of the New Testament which is quite difficult to interpret. Many debates have arisen from biblical scholars in interpreting this passage. Theological pre-assumptions can divert the interpretation of the text. The systematic theological approach can lead the interpreter's understanding not intended by the author of the book. Biblical theology must be produced through an interpretive process that pays attention to the elements of biblical texts. In interpreting Romans 11:25-27, an interpreter needs to pay attention to textual, contextual, intertextual and theological elements. Thus Romans 11:25-27 is not interpreted in the lens of systematic theology (soteriology, ecclesiology and eschatology), but pays attention to the text and the final format of the book. Thus, there is no need to continue the debate on predestination and the nature of the church in relation to Israel in both a pastoral and academic context. Understanding Romans 11:25-27 makes believers active in preaching the gospel to implement God's great plan for the church and Israel. Ultimately, God is glorified by the two communities that God has chosen.